Common Bed Bugs: Non-Viable Hosts for Trypanosoma rangeli Parasites - Sanam Meraj; Phillip Phung; Kelvin Lau; Carl Lowenberger; Gerhard Gries (Cells)
The hemoflagellate parasite Trypanosoma rangeli is transmitted by triatomine kissing bugs and may co-infect humans together with its Chagas disease-causing congener T. cruzi. Using real-time quantitative polymerase chain reaction (RT-qPCR) and antimicrobial assays, we studied (i) the temporal and spatial distribution of T. rangeli in common bed bugs, Cimex lectularius, following oral ingestion and hemocoelic injection of T. rangeli, and (ii) the immune responses of bed bugs induced by T. rangeli infections. Irrespective of infection mode, no live T. rangeli were present in the bed bugs’ hemolymph, salivary glands, or feces. On day 1 following infection, the bed bugs strongly upregulated the antimicrobial peptide CL-defensin. Following hemocoelic injection of T. rangeli, live parasites were absent in any bed bug tissues examined throughout the 10-day study period. The ingestion of T. rangeli-infected blood had no significant effect on bed bug survival. Our findings indicate that bed bugs disable the development of T. rangeli within their body, in stark contrast to triatomine kissing bugs, which allow the development and transmission of T. rangeli. Our findings help unravel the intricate relationships between bed bugs and trypanosomes, and they contribute to our understanding of vector biology.